(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Paroxysmal nocturnal hemoglobinuria (PNH) resulting from failure of expression of anchoring protein glycosylphosphatidylinositol (GPI), is an uncommon acquired hemolytic anemia manifested by hemoglobinuria, abdominal pain, smooth muscle dystonia, fatigue and thrombosis. Pregnancy with PNH is rare, and studies showed an increased risk of foetomaternal complications even death due to worsening cytopenias and consequent thrombosis. Here we reported a case of PNH in pregnancy. Mrs. Nasima, aged 25 years, para: 0+0, was diagnosed as a case of PNH by flowcytometry analysis on granulocytes about 1 year 3months back. Her pregnancy was no planned and she was not on antenatal care but took consultation from haematologist time to time. Her Hb level was 7-8gm/dl throughout pregnancy and needed repeated blood transfusion for anaemia. She was referred from a nearby clinic at 37 weeks of pregnancy with PROM and labour pain to the Foetomaternal medicine wing of Obs & Gynae department of BSMMU. On admission she was mildly icteric. She was treated with steroid as per consultation of haematologist. Due to failure of progress of labour emergency caesarean section was done under spinal anesthesia and a low birth weight female baby of 1.6 kg was delivered. One unit of blood transfusion was given post operatively. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 111-115